Radiotherapy in the treatment of epididymal adenocarcinoma - case report - Soumarová, Renata; Maňásek, Viktor; Perková, Hana; Ferák, Ivan (Onkologie, 2012)
BACKGROUND: Primary epididymal carcinoma is an extremely rare disease with a bad prognosis. We describe the first report of radiotherapy for definitive treatment of such a tumour. CASE REPORT: A 35-year-old man with a tumour of the epididymis underwent orchiectomy and elective retroperitoneal lymphadenectomy. Adenocarcinoma of the epididymis and lymph node metastasis were confirmed. The patient refused the suggested adjuvant chemotherapy and returned to our centre with a local recurrence after 6 months. We indicated palliative radiotherapy to the scrotal and groin region. Complete remission was achieved and continues 3.5 years after treatment. Late effects included teleangiectasia, fibrosis and thickening of subcutaneous tissue, and depigmentation in the groin, but the patient enjoys very good quality of life including penile erection. CONCLUSION: We presented very good results of radiotherapy in the treatment of this rare malignant disease. We achieved complete remission with a good quality of life and with tolerable chronic toxicity.
Keywords: adjuvantní radioterapie; výsledek terapie; orchiektomie; Treatment Outcome; Adult; Male; Orchiectomy; Radiotherapy, Adjuvant; lidé; dospělí; mužské pohlaví; Testicular Neoplasms; Humans; testikulární nádory